Isolation, identification and characterization of natural yeasts for brewing - Lorenzo Garrido, Alfonso; Ibeas, José I. (Biosaia: Revista de los másteres de Biotecnología Sanitaria y Biotecnología Ambiental, Industrial y Alimentaria, 2021)
The beer market has experienced a significant growth in recent years, impulsed by the consumption of a greater variety of beers with different characteristics. The role of yeasts in the aromatic and flavor profile of beer is essential since they are responsible for many of the aromatic compounds present in the final fermented product. For this reason, in this work we have focused on the identification and characterization of yeasts, mainly Saccharomyces cerevisiae, present in different grape musts and other natural media. The yeasts found will allow us to create a collection of yeasts with a particular fermentative potential for the brewing beer. We got samples from grape musts of different companies from different locations with a natural autochthonous microbiota, and carry out a spontaneous fermentation at different temperatures (16, 18, 20 and 24º C) for an approximate period of 2 weeks, generating a differential evolution of yeasts that have been analysed through CO2 evolution and subsequently isolated yeast samples on selective media (YPD, YNBlys, YPD + malt extract + 5% alcohol) and molecularly analyzed by microsatellite analysis (SSR), which allowed us to identify and differentiate strains of the species Saccharomyces cerevisiae. The strains found are now being subjected to different tests: maltose fermentation, growth curves and flocculation; the results of which will allow us to select potential candidates according to the metabolic, phenotypic and growth profile, for the production of beer. As a final test, we will carry out a brewing with the selected strains, malt extract and commercial hops. Likewise, we will carry out a tasting in which we will evaluate the organoleptic profile of each of them and the potential of each inoculated strain in compare to comercial brewing yeasts.